Examining the association between serum IgG of oral bacteria and metabolic syndrome - Yang, Zhe-Yu; Fang, Wen-Hui; Kao, Chia-Chun; Chen, Wei-Liang (Frontiers in Medicine, 2022)
Aim This investigation explored the relationship between oral bacteria and metabolic syndrome (METS). Materials and Methods There were 4,882 subjects enrolled in this cross-sectional study from the NHANES III database. The severity of periodontitis was classified into mild, moderate and severe. We measured oral bacterial antibodies. We examined the relationship between serum immunoglobulin G (IgG) antibodies of oral bacteria and METS via performing multivariate regression analysis. Mediation analysis of oral bacteria on the correlation between periodontitis and METS was also executed. Results After adjusting for covariates, the serum IgG antibodies of P. nigrescens, E. corrodens, and E. nodatum were associated with the presence of METS (p = 0.006, p = 0.014 and p = 0.018, respectively). Furthermore, serum IgG antibodies of P. intermedia, T. forsythia and V. parvula were positively associated with the presence of METS (p = 0.001, p = 0.011, and p = 0.002, respectively) and ≥4 features of METS (p = 0.019, p = 0.025, and p = 0.02, respectively). P. intermedia IgG mediated 11.2% of the relationship between periodontitis and METS. Conclusion Serological markers of oral pathogens were correlated with the presence and the number of METS features after multivariable adjustment. Oral bacteria acted as a mediator of the correlation between periodontitis and METS. Our study provided a biologically plausible explanation for the association between periodontitis and METS, which provides a comprehensive evaluation of periodontitis.